A presença cultural dos imigrantes haitianos, a partir de 2010, na cidade de Cascavel - PR / Prezans kiltirèl imigran ayisyen yo, an 2010, nan vil Cascavel - PR - Werlang , Mirtes Teresinha (2021)
It is considered in this research that the immigrant goes through a process of constant acceptance of cultural, ideological and political differences when seeking to adapt to local differences. This study aims to investigate the Haitian cultural presence in the municipality of Cascavel, state of Paraná, starting from the decade of 2010. Therefore, it uses Phenomenology, Oral History and the foundations of Humanistic Cultural Geography to discuss migratory flows in the contemporary scenario. In context, the history of Haiti and the factors related to demographic migration of that country will be detailed; the grounds for which the immigrants chose the Brazilian Nation and the attactions for the municipality of Cascavel. In that regard, the social and cultural relations of the immigrants with the local population will be analyzed. The life story, the cuisine and language were the themes that allowed a peculiar analysis of the Haitian cultural presence in the municipality. It is concluded that it is a recent migratory flow, where the existance of an affective connection with the country of origin and a cultural practice, habits and customs (language and cuisine) that the Haitian immigrant cultivates in the interaction with his countrymen can be observed. However, there is a struggle on the part of the immigrant to integrate the local culture. It is evident a cultural interaction between Haitian and cascavelenses citizens in everyday life.